Design and cyclic behavior of a bidirectional double-hinge steel column base. (September 2022) - Wei, Jian-peng; Tian, Li-min; Guo, Yang; Qiao, Hui-yun; Jiao, Zhi-an; Bao, Yu
Abstract: A bidirectional double-hinge steel column base is proposed to optimize the deformation and load patterns of traditional column bases. Based on the validated FE analysis, the design and cyclic behavior of the double-hinge column base were comprehensively investigated. The results indicate that the double-hinge column base exhibits clear mechanical behavior. Owing to the double-hinge structure, the horizontal displacement at the bottom of the column was restricted and the stress concentration was mitigated. A double-hinge column base design was proposed and verified using finite element (FE) analysis. The methods of calculating bearing capacity and initial stiffness were accurate and reliable, with discrepancies within 10%. The energy-dissipation ratio of the steel dampers exceeded 90% when the design requirements were satisfied. The earthquake-resilient function and feasibility of the double-hinge column base have been validated.